The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/pi.4990320103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new aromatic sulfone ether polyamides containing pendant pentadecyl groups

Abstract: A series of new polyamides and copolyamides containing aromatic sulfone ether linkages was synthesized from 4,4′‐[sulfonyl‐bis(4,1‐phenyleneoxy‐3‐pentadecyl)]bisphenylamine (SPPBA) and isophthaloyl chloride (IPC), terephthaloyl chloride (TPC), bis(4‐chlorocarbonylphenyl)dimethylsilane (DMSC) and bis(4‐chlorocarbonylphenyl)diphenylsilane (DPSC) by a low‐temperature inter‐facial polymerization technique. SPPBA was prepared from 4,4′‐dichlorodiphenyl sulfone and 4‐amino‐3‐pentadecyl phenol derived from cashew‐nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…were synthesized starting from cardanol (Scheme 18). 102,126,[200][201][202][203][204][205][206][207][208][209][210][211][212][213][214][215][216] These difunctional monomers were utilized for the synthesis of a variety of high performance polymers such as aromatic polyimides, polyamides, poly(azomethine)s, poly-(amideimide)s, poly(esterimide)s, polyesters, polyhydrazides, polyoxadiazoles, etc. The effects of incorporation of pendent pentadecyl chains on solubility and thermal properties of the polymers were evaluated.…”
Section: Step Growth (Difunctional) Monomersmentioning
confidence: 99%
“…were synthesized starting from cardanol (Scheme 18). 102,126,[200][201][202][203][204][205][206][207][208][209][210][211][212][213][214][215][216] These difunctional monomers were utilized for the synthesis of a variety of high performance polymers such as aromatic polyimides, polyamides, poly(azomethine)s, poly-(amideimide)s, poly(esterimide)s, polyesters, polyhydrazides, polyoxadiazoles, etc. The effects of incorporation of pendent pentadecyl chains on solubility and thermal properties of the polymers were evaluated.…”
Section: Step Growth (Difunctional) Monomersmentioning
confidence: 99%
“…However, wholly polyarylates are insoluble and have high glass transition or melting temperatures and are hence difficult to process. The ordering and structural variations of polymer backbones decide the final properties of the polymer [4,5]. Earlier investigations showed that modified cardo groups [6,7] and pendant moieties [8][9][10][11][12] produced amorphous polyesters that dissolved in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier investigations showed that modified cardo groups [6,7] and pendant moieties [8][9][10][11][12] produced amorphous polyesters that dissolved in organic solvents. Polyesters derived from CNSLbased monomers showed relatively lower glass transition temperatures in addition to the enhanced solubility of these polyesters in some organic solvents, probably due to the plasticising effect of the pendant long pentadecyl alkyl groups [5,9]. Good melt-processability of the polymers required lower glass transition temperatures so that processing could be performed at relatively lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, while aliphatic amines have been extensively studied, only a few examples are hitherto reported for aromatic amine synthesis. These are all based on cardanol, extracted from cashew nut shell liquid, and involve S E Ar reactions. Cardanol derivatives are nitrated with nitric acid or undergo diazo coupling with the diazonium salt of sulfanilic acid. Reduction toward amine is performed in the presence of a Pd/C catalyst with hydrazine for the nitro and with sodium dithionite for the diazo group.…”
Section: Introductionmentioning
confidence: 99%